The Use of Spelling Bee Game In Teaching Vocabulary At The Seventh-Grade Students of MTs Hidayatullah Mataram - Ilham Ilham; Humaira Humaira (Linguistics and ELT Journal, 2020)
Learning English subject matter using Modal auxiliary verbs is felt difficult for students especially in creating simple sentences. Based on the results of the initial researchers' observations at SMPN 7 Mataram, English learning is still dominated by conventional learning. Therefore class VIII must be given an action in the form of more effectiveSpelling bee is a competition that asks students to spell the words as well as the sounds of a buzz. The Spelling bee is conducted orally, and it looks at contests of accuracy rather than speed. In this game, the pronouncer should allow students to ask for repetitions, sample sentences, the meaning of the word. The pronouncer has to give them the possible chance of spelling their words correctly. Regarding the definition, the researcher tries to conduct the spelling bee game in teaching vocabulary at the seventh-grade students of MTs Hidayatullah Mataram. The objective of the research is to investigate whether the use of spelling bee game has a positive effect on students' vocabulary or not, and the scope of the study only focuses on noun and verb. This research uses a quasi-experimental design and purposive technique sampling. The researcher takes two classes that are divided into an experimental and a control class. The population of the seventh-grade students consists of 50 students where the control class or VIIA consists of 25 students, and the experimental class or VIIB consists of 25 students. This research uses pre-test and post-test to collect the data. To analyze the data, the researcher uses SPSS program and manual computation in order to investigate whether the use of spelling bee game has a positive effect or not. Based on the result data  by using SPSS program shows that the mean score of the experimental class in pre-test is 50.84 which is classified as fairly score, and post-test is 80.96 is classified as Good score. The value of significance 2-tailed of Mann Whitney is 0.000 smaller than 0.05, it means that Ha is accepted. On the other hand, the manual computation shows that The value of t test = 2.800, df= 48, and t table for sig 0.05=1.677, and t table for sig 0.01= 2.406, it means that  t test is higher than t table.. Thus, the use of spelling bee game has a positive effect to the students' vocabulary at the seventh-grade students of MTs Hidayatullah Mataram in the academic year 2018/2019.